The impact factors for first impression - Huang Jiayi (SHS Web of Conferences, 2023)
Research on first impressions is crucial because of the widespread use of temperament judgments because of a lack of knowledge and their societal consequences. Until recently, however, first impressions were of dubious value, and factors affecting the formation of first impressions are being meticulously studied. This review discusses the aspects that affect first impressions and how first impressions could be subsequently altered. People have a tendency to evaluate others’ personalities merely based on their facial appearance. Subsequent experiences with an individual could only be used to support initial, rashly formed first impressions of that individual. Overgeneralization theories may explain this natural tendency. Further, stereotypes affect people’s first impressions by leading to preconceptions: people may directly refer to qualities that fit the stereotype even though the judged person does not fit the stereotype. First impressions can be revised with extra information that is highly diagnostic, reliable, or experience-reframing, and this revision can last for weeks or even months. This review also offers realistic future directions for research, including testing the generalizability of recent findings and examining how updating can reverse the impact of first impressions.